The parietal operculum preferentially encodes heat pain and not salience - Horing, Björn (PLoS Biol, 2019)
Substantial controversy exists as to which part of brain activity is genuinely attributable to pain-related percepts and which activity is due to general aspects of sensory stimulation, such as its salience, or the accompanying arousal. The challenge posed by this question rests largely in the fact that pain per se exhibits highly intense but unspecific characteristics. These therefore should be matched by potential control conditions. Here, we used a unique combination of functional magnetic resonance imaging (fMRI) and behavioral and autonomic measures to address this longstanding debate in pain research. Subjects rated perceived intensity in a sequence alternating between heat and sound stimuli. Neuronal activity was monitored using fMRI. Either modality was presented in 6 different intensities, 3 of which lay above the pain threshold (for heat) or the unpleasantness threshold (for sound). We performed our analysis on 26 volunteers in which psychophysiological responses (as per skin conductance responses [SCRs]) did not differ between the 2 stimulus modalities. Having thus ascertained a comparable amount of stimulation-related but unspecific activation, we analyzed stimulus-response functions (SRFs) after painful stimulation and contrasted them with those of the matched acoustic control condition. Furthermore, analysis of fMRI data was performed on the brain surface to circumvent blurring issues stemming from the close proximity of several regions of interest located in heavily folded cortical areas. We focused our analyses on insular and peri-insular regions that are strongly involved in processing of painful stimuli. We employed an axiomatic approach to determine areas showing higher activation in painful compared to nonpainful heat and, at the same time, showing a steeper SRF for painful heat compared to unpleasant sound. Intriguingly, an area in the posterior parietal operculum emerged, whose response showed a pain preference after satisfying all axiomatic constraints. This result has important implications for the interpretation of functional imaging findings in pain research, because it clearly demonstrates that there are areas where activity following painful stimulation is not due to general attributes or results of sensory stimulation, such as salience or arousal. Conversely, several areas did not conform to the formulated axioms to rule out general factors as explanations.